Maturidade sexual e congelabilidade do sêmen de tourinhos Gir - L, sob manejo alimentar estratégico. - Anibal Souza Felipe da Silva (2007)
Body weight (BW), scrotal circumference (SC), in natura semen characteristics (motility, vigor, mass motility, major, minor and total sperm defects) and Zebu-BSE (CAP) were evaluated in 22 young dairy Gyr bulls, from 15.6 to 26.9 months old, raised under strategical feed management, in Uberaba, Brazil. Semen samples of eight pre-selected 25 months old bulls (CAP>60 points) were cryopreserved using two different diluters: the egg yolk-lactose-glycerol (Nagase and Niwa, 1964) and the soil-lecithin (Bioxcell®) in the Brazilian freezing machine CRYOGEN®. The effects in the post-thawed semen traits (motility, vigor, major, minor and total defects, acrosome defects, swelling tails, Host and normal cells) were also evaluated. Seven semen collections were proceeded at the average ages of 18.2; 19.6; 20.4; 21.7; 22.5; 23.8 and 25 months. During the first three ones (March to May) bulls were kept exclusively in Braquiaria brizantha pastures and fed mineral [M1] (95 days); in the fourth (June), a feed adaptation for the dry season was proceeded using a feeding-lot [M1 and M3] and in the last three semen collections (July, September and October) animals were kept under feeding-lots and fed corn silage (7.2% CP, 49.5% NDF, 19.3% ADF) and concentrate (27.4% CP, 83.2% TDN), fractioned in three daily feedings [M3] (95 days). Pearson correlations were estimated among characteristics. Under M1, 86.4% of the animals were pubertal at the first semen collection and 100% in the second. For the sexual maturity analysis, data were reorganized by age intervals (15.6-18.9; 19.0-20.9- 21.0-22.9; 23.0-24.9; 25.0-26.9).The maturity percentage enhanced in function of age, SC and BW. In 15.6-18.9 months old interval, 9% of the bulls reached maturity exclusively under M1; in 21.0-22.9 and 25.0-26.9, 34.2% and 86.7% of the bulls respectively, reached maturity under the association effect of M3. There was no difference (P>0.05) in SC between 15.6-18.8 and 19.0-20.9 intervals for which semen characteristics showed low quality. From 21.0-22.9 to 25.0-26.9 the SC enhanced (p<0.05) among periods, as well as BW. All the characteristics differed (p<0.05) between 21.0-22.0 and the further interval (23.0-24.9), suggesting positive effects of age and strategical feeding-lot association in the sexually development. Mature and immature bulls differed (p<0.05) for all characteristics in 21.0-22.9, except vigor and minor defects and, in 23.0-24.0 interval, except for SC and vigor. BW and SC showed significant (p<0.05) and positive correlation (0.64) and also among all other characteristics, except minor defects being, therefore, associated to spermatic quality. Average CAP in 25.0-26.9 interval was 76.1 points; 81.8% of the bulls showed CAP>60, one was immature and three reached the highest score (CAP = 100). There were differences (p<0.05) in all characteristics when in natura and post-thawed semen were compared, except for major defects. Between diluters, there were differences (p<0.05) in motility, vigor, swelled tails and Host. Nagase and Niwa´s diluter reached the best results. There was variation for puberty and sexual maturity expression among bulls in this work, even under adequate feed management.